PEMBUATAN SELAI LEMBARAN TERONG BELANDA (The Making of Slice Jam from Belanda Eggplant) - MS, Latifah; Nurismanto, Rudi; Agniya, Choirunnissa (UPN VETERAN JAWA TIMUR, 2011)
The Belanda eggplant is one of multipurpose fruit commodity, classified as a commercial commodity and has a cheap price, especially in the harvest season. The Belanda eggplant including climateric fruit have sour taste, contains many useful nutrients for health, the nutrient content of which is vitamin C, antioxidants, vitamin E, and many others. The addition of pectin and sorbitol can improve the quality of physical, chemical, and organoleptic slice jam. The research method used Completely Randomized Design(CRD) factorial pattern with two factors and three replications.The first factor: the addition ofpectin(0.25%, 0.50%, 0.75%, 1.00%), and the second factor: the addition of sorbitol(5%, 10%, 15%, 20%). The results showed the addition of pectin treatment of 0.25% and the addition of sorbitol15% yield of acceptable slice jam consumers. The treatment resulted in water levels 21.169%, 28.444% antioxidant activity, gel density 3.273 mm/gr.sec, 60.433% yield, flavor (neutral) 4.50 and texture (like) 6.67 .Key words : slice jam, Belanda eggplant, pectin, sorbitol